Seni Kaligrafi: Peran dan Kontribusinya Terhadap Pengembangan Peradaban Islam - Sikni Sari Siagian -; Al Halim Kusuma (Yayasan Haiah Nusratul Islam, 2024)
The art of calligraphy has played an essential role in the history and development of Islamic civilization. The aim of this research is to review the contribution of calligraphy art to the development of culture, religion and science in Islamic civilization. Calligraphy is a form of visual art that is highly valued in the Islamic tradition. Calligraphy not only functions in the field of decoration, but it is also an intermediary in conveying religious messages and moral values. In this research method using historical and textual analysis, researchers found that the art of calligraphy enlarges the intellectual and spiritual life of Muslims, and also becomes an important tool in spreading Islamic teachings. Calligraphy participated in the development of Islamic art and architecture, publishing monumental works that combined aesthetic beauty and depth of religious meaning. This research shows that the art of calligraphy is not only a cultural heritage that must be preserved, but calligraphy also has a sustainable connection in the modern context.